Use of Continuous Glucose Monitors to Manage Type 1 Diabetes Mellitus: Progress, Challenges, and Recommendations - Friedman JG; Cardona Matos Z; Szmuilowicz ED; Aleppo G (Dove Medical Press, 2023)
Jared G Friedman,* Zulma Cardona Matos,* Emily D Szmuilowicz, Grazia Aleppo Division of Endocrinology, Metabolism and Molecular Medicine, Feinberg School of Medicine, Northwestern University, Chicago, IL, USA*These authors contributed equally to this workCorrespondence: Grazia Aleppo, Division of Endocrinology, Metabolism and Molecular Medicine, Feinberg School of Medicine, Northwestern University, 645 North Michigan Avenue, Suite 530, Chicago, IL, 60611, USA, Tel +1 312 926 5431, Fax +1 312 926 8693, Email aleppo@northwestern.eduAbstract: Type 1 diabetes (T1D) management has been revolutionized with the development and routine utilization of continuous glucose monitoring (CGM). CGM technology has allowed for the ability to track dynamic glycemic fluctuations and trends over time allowing for optimization of medical therapy and the prevention of dangerous hypoglycemic events. This review details currently-available real-time and intermittently-scanned CGM devices, clinical benefits, and challenges of CGM use, and current guidelines supporting its use in the clinical care of patients with T1D. We additionally describe future issues that will need to be addressed as CGM technology continues to evolve.Keywords: continuous glucose monitoring, type 1 diabetes, time in range, hemoglobin A1c